Association Between Vitamin D Receptor Polymorphism and the Response to Helicobacter Pylori Treatment - Abo-Amer YEE; Mohamed AA; Elhoseeny MM; Rezk SM; Abdel-Salam S; Alrohaimi AH; Abdelgeliel AS; Alzahrani SS; Jafri I; Alqahtani LS; Fayad E; Fakhry M; et al. (Infection and Drug Resistance, 2023)
Yousry Esam-Eldin Abo-Amer,1 Amal Ahmed Mohamed,2 Mohamed Mahmoud Elhoseeny,3 Samar M Rezk,4 Sherief Abdel-Salam,5 Abdulmohsen H Alrohaimi,6 Asmaa Sayed Abdelgeliel,7 Seham Saeed Alzahrani,8 Ibrahim Jafri,8 Leena S Alqahtani,9 Eman Fayad,8 Mohamed Fakhry,10 Moataz Yousry Soliman11 1Mahala Hepatology Teaching Hospital, Hepatology& Gastroenterology Department, Gharbia, Elgharbia, Egypt; 2National Hepatology & Tropical Medicine Research Institute, Department of Biochemistry, Cairo, Egypt; 3Department of Internal Medicine, Faculty of Medicine, Suez University, Suez, Egypt; 4Department of Clinical Nutrition, Mahalla Hepatology Teaching Hospital, El-Mahalla El-Kubra, Elgharbia, Egypt; 5Department of Tropical Medicine, Hepatology & Gastroenterology Unit, Faculty of Medicine, Tanta University, Tanta, Egypt; 6Department of Pharmacy Practice, College of Pharmacy, Shaqra University, Shaqra, 11961, Saudi Arabia; 7Department of Botany & Microbiology, Faculty of Science, South Valley University, Qena, 83523, Egypt; 8Department of Biotechnology, College of Science, Taif University, Taif, 21944, Saudi Arabia; 9Department of Biochemistry, College of Science, University of Jeddah, Jeddah, 23445, Saudi Arabia; 10Department of Gastroenterology, Hepatology and Infectious Diseases, Faculty of Medicine, Al-Azhar University, Asyut, Egypt; 11Department of Hepatology, Gastroenterology and Infectious Diseases, Faculty of Medicine, Al-Azhar University, Cairo, EgyptCorrespondence: Sherief Abdel-Salam, Department of Tropical Medicine, Hepatology & Gastroenterology Unit, Faculty of Medicine, Tanta University, El-Bahr Street, Tanta, Egypt, Tel +201147773440, Email sheriefabdelsalam@yahoo.comBackground & Aims: This research aimed to determine how variations in the vitamin D receptor gene affected the response of H. pylori infections to eradication therapy.Patients and Methods: On 105 adult H. Pylori-positive patients, a prospective cohort study was carried out. PCR was used to genotype all patients’ VDR gene polymorphisms. The patients in the study received standard triple eradication medication (clarithromycin 500 mg, amoxicillin 1000 mg, and omeprazole 20 mg) twice daily for 14 days. A stool test for H. pylori Ag was conducted 4 weeks following the end of treatment.Results: In our study, the usual triple therapy’s H. pylori eradication rate was 75.2%. The successful eradication of H. pylori and VDR rs 2228570 gene polymorphisms was more prevalent in CT gene polymorphism (64.6%) compared to non-responders (19.2%), while treatment failure was more prevalent in CC gene polymorphism (73.1% in non-responders compared to responders 24.1%), which is statistically significant. In regards to the eradication of H. pylori and VDR rs7975232 gene polymorphisms, the success of eradication was more prevalent in AC gene polymorphism (54.4%) vs non-responders (30.4%), while all patients (14) with gene AA (17.7%) are responders to standard treatment, while the failure of treatment was more prevalent in CC gene polymorphism (69.2% in non-responder vs 27.8% in responders) which is statistically significant. Our findings demonstrated a strong correlation between patients’ responses to H. pylori treatment and polymorphisms in the VDR gene (ApaI and TaqI) (P 0.05).Conclusion: As far as we are aware, this is the first study to identify a potential link between the FokI and Apal VDR polymorphism and treatment response in H pylori-positive patients. To evaluate the findings, more research with larger number of patients and different population is required.Keywords: Helicobacter, infection, gene, polymorphism, response, eradication